Quantifying Preferences for CAR‐T Compared to Standard of Care as a First‐Line Treatment Among Patients With Multiple Myeloma - Jessie Sutphin; Thomas W. LeBlanc; Ellen Janssen; Laura Hester; Matthew J. Wallace; F. Reed Johnson; Shelby D. Reed (Cancer Medicine)
ABSTRACT Background CAR‐T therapy is approved for the treatment of relapsed refractory multiple myeloma (MM) and is being studied for newly diagnosed MM (NDMM). The use of novel therapies in early‐line MM raises questions on the acceptability of upfront risks in exchange for extended relapse‐free periods without the treatment burden and limitations on daily activities associated with maintenance therapy. Methods A discrete‐choice experiment was designed to elicit adults' preferences for hypothetical NDMM treatments. Benefits included time to relapse and reduction of treatment impact on daily activities. Severe adverse events were included to better understand patient preferences for rare but significant events. Results On average, extending the time to relapse from 3 years (with moderate limitations on daily activities) to 5 years (without limitations) was three times more important than avoiding a 20% risk of hospitalization due to severe ICANS/CRS. Analysis revealed three latent preference classes: a benefit–risk trading class (65%), a class (28%) unwilling to accept increases in short‐term treatment‐related mortality, and a class (7%) that provided statistically uninformative data. For the trading class, for two additional relapse‐free years with minor limitations, all else equal, patients would accept up to a 30% risk of severe ICANS/CRS‐related hospitalization along with 0% risk of treatment‐related mortality. Alternatively, they would accept up to an 8% risk of treatment‐related mortality with a 0% risk of severe ICANS/CRS‐related hospitalization, or various combinations of lower AE risks. Conclusion These results reveal preference heterogeneity among MM patients and the importance of effective communication about the benefits and risks of novel therapies.